2014
DOI: 10.1007/s11041-014-9750-9
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Thermal Analysis to Study the Structure and Properties of Roll Steels

Abstract: The possibility of the application of thermal analysis to the selection of a method for heat-treating roll steels is examined. The temperatures that should be used for the solution annealing and quenching of steel 60Kh2SMF produced by electroslag remelting are determined.Given the stiff competition in the current market for rolled products, attention is being focused on the products' quality and the cost-effectiveness of the production process. To a large extent, these two factors depend on the condition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Analysis of acoustic methods showed that the most satisfactory method to assess the quality of a roll and to control the presence of defects (for example, cracks) in the surface layer of work rolls for cold-rolling mills is the echo method in jet variant. This method is a relatively simple way to detect defects of a mill roll [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of acoustic methods showed that the most satisfactory method to assess the quality of a roll and to control the presence of defects (for example, cracks) in the surface layer of work rolls for cold-rolling mills is the echo method in jet variant. This method is a relatively simple way to detect defects of a mill roll [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%